Vibration reduction of lightweight structures through adjustable damping and stiffness properties at their interfaces - Emil Heyden; Philipp Hüttich; Lukas Bunk; Dieter Krause (Journal of Low Frequency Noise, Vibration and Active Control)
This paper presents the vibration reduction of lightweight components by adjusting the mechanical properties of their boundary conditions in vibration test rigs. The variable boundary conditions are achieved by adjustable impedance elements, which are mechanical elements that can change their stiffness and damping behavior separately and are designed for use in vibration testing. A new generation of an adjustable impedance element is presented in this publication and its use in a large component test environment. The influence of the adjustable mechanical properties of the interfaces on an aircraft partition is shown. A holistic finite element model is presented to predict the interactions between the adjustable interfaces and the test object. A vibration reduction of about 65% compared to current rigidly designed joints is achieved. The influence of vibration on the partition is investigated experimentally for different stiffness and damping ranges and the corresponding simulation model is validated.